Affective Tone in Medical Encounters and Its Relationship With Treatment Adherence in a Multiethnic Cohort of Patients With Rheumatoid Arthritis. Issue 4 (June 2015) - Street, Richard L.; Marengo, María F.; Barbo, Andrea; Lin, Heather; Gonzalez, Araceli Garcia; Richardson, Marsha N.; Suarez-Almazor, María E.
<x xml:space="preserve">Abstract</x> Background Tone of voice in communication between patients and rheumatologists may offer insight into problems of treatment adherence in patients with rheumatoid arthritis. Objective The aim of this study was to evaluate physician-patient affective vocal tone within the medical encounter and its relationship to treatment adherence in ethnically diverse patients with rheumatoid arthritis. Methods The consultations of 174 patients with rheumatoid arthritis were audio recorded at a baseline visit. Of these, 135 completed follow-up adherence measures at 3 months. The positive and negative affective tones of patients, physicians, and interpreters (and distressed tones of patients and interpreters) were assessed using the Roter Interaction Analysis System affective communication scale. Treatment adherence was evaluated at baseline and at 3 months using the Compliance Questionnaire Rheumatology. Results A total of 117 baseline consultations were in English (n = 42, 36, and 39 white, African American, and Hispanic patients, respectively), 24 in Spanish, and 33 with an interpreter (total = 174). Patients reporting poorer adherence were rated as having more distressed affect and less positive affect than patients reporting greater adherence. Physicians expressed more positive affect to more educated patients. Physicians and patients reciprocated one another's positive and negative affect. Controlling for baseline adherence, physician negative affect predicted greater adherence at 3 months for Hispanic patients, regardless of language choice, compared with white patients. Conclusions Patients' affective tones offer clues to problems patients may have with treatment adherence and well-being. More research is needed regarding why physicians' expression of negative affect may facilitate adherence for some groups of patients.